(1)H NMR spectra of alcohols in hydrogen bonding solvents DFT/GIAO calculations of chemical shifts - Lomas, John S (Magnetic resonance in chemistry : MRC, 2016)
Copyright © 2015 John Wiley & Sons, Ltd.